Suicidal thoughts and attempts in First Nations communities: links to parental Indian residential school attendance across development. (20th June 2018) - Bombay, A.; McQuaid, R. J.; Schwartz, F.; Thomas, A.; Anisman, H.; Matheson, K.
Abstract: The Indian residential school (IRS) system in Canada ran for over a century until the last school closed in 1996. Conditions in the IRSs resulted in generations of Indigenous children being exposed to chronic childhood adversity. The current investigation used data from the 2008–2010 First Nations Regional Health Survey to explore whether parental IRS attendance was associated with suicidal thoughts and attempts in childhood, adolescence and in adulthood among a representative sample of First Nations peoples living on-reserve across Canada. Analyses of the adult sample in Study 1 (unweighted n =7716; weighted n =186, 830) revealed that having a parent who attended IRS was linked with increased risk for suicidal thoughts and attempts in adolescence and adulthood. Although females were negatively affected by having a parent who attended IRS, the link with suicidal ideation in adulthood was greater for males. Analyses of the youth sample in Study 2 (unweighted n =2883; weighted n =30, 190) confirmed that parental IRS attendance was associated with an increased risk for suicidal ideation and attempts. In contrast to the adult sample, parental IRS attendance had a significantly greater relation with suicidal ideation among female youth. A significant interaction also emerged between parental IRS attendance and age in the youth sample, with the influence of parental attendance being particularly strong among youth ages 12–14, compared with those 15–17 years. These results underscore the need for culturally relevant early interventions for the large proportions of Indigenous children and youth intergenerationally affected by IRSs and other collective traumas.